INTEGRATING THE PROGRAM OF SCHOOL CURRICULUM AND PESANTREN EDUCATION; CASE STUDY ON THE PESANTREN LOCATED IN THE MADRASAH AT MALANG CITY - Nur Ali (Abjadia : International Journal of Education, 2020)
As a modern Islamic educational institution, Madrasa (Islamic boarding school) has shifted into a public school that has Islamic identity and the issue of restructuring its curriculum is assumed as a deteriorating factor in religious aspects for its graduates. Related to this, Madrasa have responded by carrying out a curriculum program development through the integration of Madrasa curriculum program and Ma’had education (Islamic dormitory). This article aims to describe the background of the integration of Madrasa curriculum program and the education in Ma’had as well as the activities and literacy that determine the success of the curriculum program integration. The data obtained from the observation, interview, and documentation were then analyzed through reduction, display, and verification phases. Afterward, the data triangulation was also conducted. It led to several findings. First, the integrated curriculum program was carried out based on the vision and mission of both Madrasa and Ma’had, and the advance of religious study and science. Second, taklim madrasy and taklim Ma’hady (learning activity conducted in Madrasa and Ma’had) have become the determining factors for the successful implementation of the integrated curriculum program. Moreover, all guests ranging from the officials of the Ministry of Religious Affairs, visitors from other cities and overseas, the Madrasa committee, and all tutors in the Madrasa have also affected the information literacy, digital, and collaboration levels. This sudy provides suggestions to conduct the integration of the school, Madrasa curriculum program and Ma’had program in one location to develop the students’ religious behavior, tolerance, empathy, spirituality knowledge, and literacy skill.